Comparison of Synovex-S® and steer-oid® in finishing yearling steers - Brandt, Robert T., Jr.; Anderson, S.J.; Elliott, J.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Synovex-S (SS) and STEER-oid (SO) were compared in a 122-d finishing study. No differences were observed over the entire study for animal performance or carcass traits. However, in the final period (d 91-122), steers implanted with SO gained 8.4% faster (P=.17) and 8.7% more efficiently (P=.10) than steers implanted with SS, suggesting that estradiol payout in this period was less diminished for SO implants. The importance of this finding is unknown, because it is generally recommended that steers fed for longer periods of time be reimplanted midway through the finishing period to maintain maximal implant response.
Keywords: Beef; Implant; Estradiol comparison; Feedlot; Cattle